Determination of Groundwater Sensitivity Potential Using Geography Information System (GIS) Based DRASTIC Model: A Case Erzin Plain (South of Turkey) - Fatih Karaosmanoglu (Indonesian Journal of Agricultural Research, 2021)
Today, due to the rapidly increasing world population and urbanization, the amount of water is increasing exponentially in areas such as drinking, irrigation, energy, industry, etc. There is a great increase in the use of water in agriculture, especially due to the food needs of human beings. For this reason, human beings need water; They obtain water almost everywhere from above ground (springs, dams, ponds) and underground (drilling wells) water sources. Usage of groundwater is quite common in the plains, where surface water resources are insufficient. This situation; While increasing the use of pesticides and fertilizers for agricultural purposes due to irrigation, it also creates the risk of contamination of groundwater. In this study; contamination potential of groundwater in Erzin Plain was determined using Geography Information System (GIS)-based DRASTIC model. Seasonal and annual field sensitivity levels were determined by integrating current land use into this model. Accordingly, in the dry seasons of August-2006, November-2006, while the Mediterranean coast has high EC values in the vicinity of the Mediterranean coast, the area around the resort sites and the settlement area, the mountainous areas, the north of the plain and the west of Gokdere have low EC values. It has the lowest EC values by decreasing towards the north and northeast and other parts of the plain. In the study area; Although NO3 concentration varies seasonally, it is especially high in citrus growing segments with high permeability. On this change; Factors such as rainfall recharge, evaporation effect in the dry period, irrigation water recharge with the effect of land use, and the depth of groundwater depending on topography played an important role.